A controlled trial of the use of dip slides in general practice for the diagnosis of urinary infection. Issue 3 (March 1973) - Maskell, Rosalind
Abstract : A controlled trial of the use and interpretation of dip-inoculation slides for the diagnosis of urinary infection in four general practices is reported. Two slides were inoculated from each specimen, one being incubated and read in the surgery by the practitioner, the other being sent to the laboratory for incubation and interpretation. It is shown that the presence or absence of bacteriuria can be detected with a high degree of accuracy by a surgery procedure. The implications for the laboratory, the patient, and the practitioner are discussed. It is suggested that the financial saving on laboratory time and unnecessary treatment would far outweigh the outlay on apparatus and materials, and that many patients would benefit from the accurate diagnosis of urinary infection which, for a variety of reasons, is at present denied them.